Lactylation in cancer: mechanistic insights, tumor microenvironment, and therapeutic horizons - Yang, Qiang; Yang, Zhibo; Zhao, Hai (Frontiers in Immunology, 2026)
The discovery of lactylation, a post-translational modification derived from lactate, has fundamentally altered the perception of cancer metabolism. Once regarded as a metabolic waste product, lactate is now recognized as a central fuel source, a signaling molecule, and an epigenetic substrate capable of reprogramming gene expression and cellular function. Lactylation integrates metabolic reprogramming, tumor plasticity, and immune suppression, thereby orchestrating cancer initiation, progression, and resistance to therapy. This review provides a critical and integrative commentary on recent advances in lactylation biology, drawing from biochemical, epigenetic, and immunological perspectives. It synthesizes mechanistic insights into lactylation, highlights its role in tumorigenesis and the tumor microenvironment (TME), and evaluates therapeutic strategies that target lactate production, transport, and lactylation machinery. By dissecting consensus, controversies, and unresolved questions, we argue that lactylation represents both a hallmark of tumor adaptation and a potential Achilles’ heel for intervention. We further discuss future research directions, including comprehensive lactylome mapping, structural biology of lactylated proteins, microbiome-derived lactate, and clinical translation. Ultimately, lactylation is not merely a byproduct of glycolysis but a metabolic language that tumors employ to communicate, adapt, and thrive. Decoding this language may open new frontiers in cancer therapy.